The Satisfaction Level of Local Islands Public Transportation Service: A Case Trans Batam - Rizska Dwi Kartika; Adinda Fajarika Akhir (Fakultas Teknik Sipil dan Perencanaan, 2023)
Public transport, defined in this paper as high-capacity vehicle sharing with fixed routes and schedules, is the backbone of urban transportation systems in global cities. The problems of Trans Batam are the lack of information about the availability of running buses, some inadequate bus stops, routes that are still not extensive, comfort and payment process. The purpose of this paper is to determine the level of satisfaction of Trans Batam users both for the local community and visitors who have just been to Batam. This research uses SERVQUAL method. Trans Batam city bus service providers need to improve their performance especially on indicators that have high gaps in order to continue to be the choice of users and compete with other public transportation.